PEMANFAATAN PEMASARAN DIGITAL DAN PERDAGANGAN ELEKTRONIK DALAM PEMASARAN UMKM SIOMAY CAKRABUANA DI ERA NEW NORMAL - Silviana Ayu Puspandari; Sukamarriko Andrikasmi; Furqon Ibnu Qolby; Yazlyn Nurhaliza; Fira Safitri; Farah Amalia Yulisa; Bunga Shalza Filza; Hanief Azzam Syauqi Mayfi; Efrina Efrina; Nur Azizah Melani; Albert Doni L. Tobing (Fakultas Teknik, Universitas Bangka Belitung, 2023)
The new normal era is the perfect place for the government and society to solve economic problems caused by a disease called COVID-19. Taking advantage of this new normal era, the Riau University KKN group took the initiative to visit UMKMs with the aim of reviving the economy of UMKM agents through digital marketing strategies using social media and electronic commerce. The implementation method used in this program is participatory method. The target partner is one of the MSMEs in West Sidomulyo Village, Pekanbaru City, namely UMKM Siomay Cakrabuana. The partner has a problem in the form of an economic downturn due to the closure of several branches due to the COVID-19 event. The result of this activity is that the KKN group received an enthusiastic and positive response from UMKM owners, as well as improving the economy of UMKM agents by implementing digital marketing and e-commerce as an effective and efficient communication and marketing tool in business activities. This is expected to be a solution to the main goal so as to enable them to maintain their own economy.